Deteccion y evaluacion de B-Exotoxina en cepas nativas de Bacillus thuringiensis - Baro, Y.=700 1 Botta, E.
(Es, En)
Ilus., 15 ref.
Keywords: BACILLUS THURINGIENSIS; EXOTOXINAS; ENSAYO BIOLOGICO; CUBA; B-EXOTOXINA; EXOTOXINA TERMOESTABLE